2001
DOI: 10.1097/00042752-200110000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Injection in Early Treatment of Lateral Epicondylitis

Abstract: A corticosteroid injection does not provide a clinically significant improvement in the outcome of LE, and rehabilitation should be the first line of treatment in patients with a short duration of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(72 citation statements)
references
References 18 publications
2
65
0
5
Order By: Relevance
“…A total of four RCTs of variable quality (125 participants) were included in the review. 112,115,118,119 Only two RCTs were judged to be of sufficient quality to be considered in this overview. 112,118 Neither severity of lateral epicondylitis nor details of co-interventions were reported in any of the studies.…”
Section: Exercisesmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of four RCTs of variable quality (125 participants) were included in the review. 112,115,118,119 Only two RCTs were judged to be of sufficient quality to be considered in this overview. 112,118 Neither severity of lateral epicondylitis nor details of co-interventions were reported in any of the studies.…”
Section: Exercisesmentioning
confidence: 99%
“…56,60 One high-quality review 60 included 12 RCTs (1171 participants) examining the effect of GCIs on lateral epicondylitis. 38,40,50,116,118,[120][121][122][123][124][125][126] Severity of tennis elbow (mean pain score before treatment) was reported for six of the included studies and ranged from 49 to 83 on a visual analogue scale (VAS) score (0-100). Co-interventions were not mentioned.…”
Section: Glucocorticoid Injectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,20 Furthermore, a corticosteroid injection early in the course of LE (less than 4 weeks) does not significantly change the outcome at 4 weeks, 8 weeks, or 6 months. 21 A recent systematic review 2 exploring the effectiveness of electrophysical modalities for treatment of LE has shown that there is moderate evidence for effectiveness of ultrasonography (protocol obtain from the original study: 1 MHz, 1:4, 1 W/cm 2 , 10 minutes per session, 2 to 3 times weekly, for a total of 10 treatments) 22 vs placebo in the medium term. There is limited evidence for the effectiveness of noxious-level electrical stimulation over tender points or low-or high-frequency transcutaneous electrical nerve stimulation on acupuncture points vs, respectively, placebo and sham transcutaneous electrical nerve stimulation in the short term (2 weeks).…”
Section: Managementmentioning
confidence: 99%
“…11 There is no supportive evidence either topical or oral NSAIDS are the treatment option for common extensor tendinopathy. Pattanittum et al 2013 reviewed 15 trials comparing topical NSAIDs or oral NSAIDS versus placebo.…”
Section: Discussionmentioning
confidence: 99%